Efficacy and safety of apatinib monotherapy for patients with advanced breast cancer: a systematic review and meta-analysis - Huang, Xuchen; Hu, Xuhua; Yi, Tongbo (Frontiers in Oncology, 2022)
Background: Patients with advanced breast cancer usually have poor prognosis. Apatinib is a small molecule tyrosine kinase inhibitor, and the reports regarding the efficacy and safety of apatinib monotherapy for advanced breast cancer in the current literature are controversial. Therefore, we performed a systematic review and meta-analysis to collect and pool efficacy and safety data of apatinib monotherapy for advanced breast cancer with the aim of providing up-to-date evidence to aid clinical practice. Methods: This study was registered at PROSPERO (CRD42020190049). Three literature databases, including PubMed, EMBASE, and Cochrane Library, were searched. For evaluating efficacy, the objective response rate and disease control rate were extracted or calculated. Safety was evaluated in terms of the proportions of patients with grade 3 or 4 treatment-related adverse events. The pooled proportions of the outcomes and their 95% confidence interval were shown. The Kaplan-Meier curves of overall survival and progression-free survival were pooled from the extracted data of the included studies. Furthermore, pooled medians for overall survival and progression-free survival were calculated. A p value of < 0.05 was considered statistically significant. Results: Six studies were included and deemed eligible for further quality evaluation and analysis. The pooled objective response rate and disease control rate were 20.4% and 71.6%, respectively. The pooled proportions of four hematologic adverse events ranged from 2.6% to 6.9%. The pooled proportions of hypertension, hand-foot syndrome, transaminase increased, and proteinuria ranged from 4.1% to 24.3%, and other nonhematologic adverse events were <1%. The pooled median progression-free survival and overall survival were 4.00 and 10.43 months, respectively, in cases of advanced breast cancer treated with apatinib. Conclusions: This study confirms the reliable efficacy of apatinib monotherapy for advanced breast cancer. However, nonhematologic grade 3-4 adverse events, especially hypertension, are more frequently observed during apatinib treatment than during treatment with other tyrosine kinase inhibitors, such as sunitinib or sorafenib.